Crawford, Lily (London, 2011)
2011 "Crawford, Lily", 2011, HistoryTalk Lily arrived in the UK in 1951 from Jamaica. She had considerable training as a beautician in Jamaica and found success hairdressing, introducing a hair-straightening technique to her African-Caribbean clients in 1950s London. She made clothes before she retrained and then found success as a photographer in the 1960s.